How A Team Games Tournament Method Improves Injury Handling Behavior among Those who Participate in Extracurricular Sports - Wahyuni, Erna Dwi; Fridayanti, Regina Dwi; Ni’mah, Lailatun (International Journal of Psychosocial Rehabilitation, 2020)
— Individuals who participate in extracurricular sport (hereafter sports extracurricular members) are required to handle injuries. But, members’ knowledge of ways to handle injury is still lacking. This study aimed to analyze the effectiveness of health education using a Team Games Tournament (TGT) method to enhance extracurricular members’ behavior in terms of handling injuries. This study used a quasi-experimental pretest-posttest design. A simple random sampling technique was chosen to recruit respondents according to the inclusion criteria. There were 64 sports extracurricular members at Junior High School level involved in the study. The dependent variables were injury handling behavior, consisting of knowledge, attitude, and practice; the independent variable of this study was the TGT method. This study used a questionnaire related to injury knowledge, attitude towards treating injury, and injury treatment. Data were analyzed used the Wilcoxon Signed Rank and Mann-Whitney test with a significance level of p <0.05. The research results indicate that the TGT method against increased knowledge (p = 0.000), attitude (p = 0.000) and action (p = 0.000) in the treatment group. There was a significant difference between the treatment group and the control group in terms of knowledge (p = 0.000), attitude (p = 0.000) and action (p = 0.000). This study showed that using TGT in health education is effective in changing sports extracurricular members’ behavior in terms of treating injuries.